Degas, Edgar - René de Gas (Zeno Fotografie) - Degas, Edgar (NC, 2026)
Degas, Edgar: René de Gas
Licence indiquee par Wikimedia Commons
Keywords: Degas; Peintur; Peintures; Tableaux; Musée; musée national